PENGARUH BAURAN PEMASARAN SYARIAH TERHADAP KEPUTUSAN PEMBELIAN PRODUK BUSANA MUSLIM: (STUDI DESKRIPTIF DI KONVEKSI RIKI KARSONO BATUJAJAR, BANDUNG BARAT) - Anggraeni, Reni; Ma’mun, Saepul; Maryati, Maryati (Jurnal Pelita Nusa, 2024)
This research is motivated by the importance of the marketing mix as a tool for companies to elicit the desired response from the target market and compete with similar companies. The aim of this study is to examine the influence of the Sharia marketing mix on purchasing decisions for products at Riki Karsono Convection, Batujajar, West Bandung. The research method used is a survey with a quantitative approach, employing SPSS Version 26.0 for data analysis. The population of this study consists of 14,171 consumers of Riki Karsono Convection. A simple random sampling technique was used to obtain a sample of 100 respondents. Data analysis was conducted using simple regression. The t-test results show that the Sharia marketing mix variable has a t-value of 20.518 ≥ t-table 1.984, indicating a positive and significant influence on purchasing decisions. The correlation coefficient (R) of 0.901 indicates a very strong relationship between the Sharia marketing mix and purchasing decisions. The coefficient of determination (adjusted R square) of 0.811 suggests that 81.18% of the variation in purchasing decisions is explained by the Sharia marketing mix, while the remaining 18.82% is influenced by other factors not examined in this study.